Perception of the main caregiver on the limiting factors of using consistencies for feeding patients with dysphagia: systematic review - Vargas García, Miguel Antonio; Grajales Gómez, Laura Daniela; Delprado Aguirre, Fernando (Revista de Investigación en Logopedia, 2022)
Modifying the consistency of food allude to the reconfiguring of food texture to inhibit the risks in the transport of the food bolus presented by patients with dysphagia. In the management of dysphagia at home, the handling, preparation and support of food is carried out by a family member / main caregiver who, occasionally, does not know or interpret considerations for the management of consistencies. The objective of this systematic review was to document the limiting factors of the consistency modification strategy as a follow-up and support resource for dysphagia care. To do this, the PRISMA methodology was followed, conducting a search in the ScienceDirect, Virtual Health Library (VHL) and Scielo databases to identify articles published between 2016 and 2021. 9 studies were selected in English and Spanish, which met all the inclusion criteria and link the perception of the main caregiver in relation to the modification of consistencies for the management of dysphagia. This review synthesizes the most up-to-date data on consistency management by the caregiver in seven work categories related to knowledge of dysphagia, evidence of signs and symptoms, understanding of the consistency modification strategy, costs, biopsychosocial factor of the diet, psychosocial state of the patient and professional support. Future studies are proposed to deepen these issues.
Keywords: Deglutition Disorders; Speech; Language and Hearing Sciences; Caregivers; Rehabilitation; Diet